2015
DOI: 10.1063/1.4938194
|View full text |Cite
|
Sign up to set email alerts
|

Shape change and Peierls barrier of dislocation

Abstract: Shape change and Peierls barrier of dislocation are investigated theoretically in the framework of the improved Peierls-Nabarro model in which the lattice discreteness is considered fully. We found that the dislocation will become narrow as it moves from the energy valley to the barrier top. An expression for the Peierls barrier is proposed based on our calculations without the rigid translation assumption. The results enable us to relate the Peierls stress to the bulk properties of crystals directly and can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…However, referring to the solution of the original P-N equation and considering that the change in interfacial spacing has virtually no effect on the solution of Eq. ( 9), we can be obtain the following solution: [20] s r…”
Section: Applicationmentioning
confidence: 99%
“…However, referring to the solution of the original P-N equation and considering that the change in interfacial spacing has virtually no effect on the solution of Eq. ( 9), we can be obtain the following solution: [20] s r…”
Section: Applicationmentioning
confidence: 99%
“…The main objective of this work is the direct determination of the lattice structure of SW defect transition state in the framework of the fully discrete Peierls theory, [24,25] and the first-principles simulation of SW defect transformation process. The fully discrete Peierls theory was developed firstly to describe dislocations in graphene, in that case this elastoplastic model is comparable with the ab initio simulation.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Later, it was found that based on the spectrum analysis the fully discrete Peierls model can be established in a model-independent way. [32][33][34] The fully discrete Peierls model can accurately predict the core structure and explore dislocation response to the applied external loading. [34][35][36] In particular, the Peierls stress can be evaluated in a consistent way in the fully discrete Peierls model.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, every dislocation in the continuum theory always splits into two different types with different core. [33][34][35][36][37] The polymorphism of dislocation core structures at the atomic scale attracts much attention. [3,4,7,[33][34][35][36][37][38] Metal aluminum (Al) is widely used in modern engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation